Horizontal jump predicts weightlifting performance - Kite, R. J.; Spence, A. (EWF Scientific Magazine, 2017)
The results of this study provide early evidence that the HJ can be used as an appropriate predictor of weightlifting performance for adults. Due to the relatively small sample size, generalisation and extrapolation should be applied cautiously. However, the results of the post hoc power analysis support the validity of the results presented here. The limited requirements of resources for the execution of the assessment provide a logistical advantage over other forms of assessment. However, the practitioner should carefully consider the relevance of this particular test to the athletes they are working with, with particular consideration to performance standard, previous experience, and sex. Furthermore, the relationships demonstrated between VJ, HJ, and 30ST with various measures of weightlifting performance provide additional evidence that these movements all share similar underpinning strength and power requirements. Therefore, training for enhanced high-force and high-velocity actions could be optimised by the inclusion of some, or all, of the exercises presented in this study.